Sustainable Agriculture and Food Security - Dr. Jayson Cola (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2021)
Sustainable agriculture is increasingly recognized as pivotal in ensuring global food security amidst growing environmental challenges. This abstract explores the intersection of sustainable agriculture and food security, highlighting key concepts, challenges, and strategies. The concept of sustainable agriculture emphasizes practices that optimize the use of natural resources while minimizing environmental impact. It encompasses techniques such as organic farming, agroforestry, and integrated pest management, all aimed at preserving soil fertility, biodiversity, and water quality. These practices not only enhance productivity but also contribute to long-term resilience against climate change. Food security, on the other hand, refers to the availability, access, and utilization of safe and nutritious food for all individuals. Achieving food security involves addressing issues of production, distribution, and consumption in a way that meets nutritional needs without compromising future generations' ability to do the same.